AUKUS: A Manifestation of Balance of Power in the Indo-Pacific Region - Farhan, Cikal Jalu Ghazy (Politeia : Journal of Public Administration and Political Science and International Relations, 2024)
This research analyzes Australia's foreign policy in the context of the Trilateral Security Pact AUKUS (Australia, United Kingdom, United States) as a manifestation of the concept of balance of power in the Indo-Pacific region. Announced on September 15, 2021, AUKUS is a trilateral agreement to strengthen diplomatic, defense, and security relations among the three countries, with Australia receiving three Virginia-class nuclear-powered submarines from the United States. The Indo-Pacific, which is geographically and economically strategic, has become a focal point of global geopolitical competition, particularly with the rise of China's influence, perceived as a threat by the United States and its allies. Through AUKUS, the United States, the United Kingdom, and Australia seek to balance power in the region by enhancing military capabilities and defense technologies, in line with neorealist theory, which emphasizes the importance of security and power equilibrium in an anarchic international system. This study employs a descriptive qualitative methodology with secondary data analysis to understand the dynamics behind the formation of AUKUS and its implications for regional stability. The findings indicate that AUKUS is a strategic response to global and regional power balancing and reflects Australia's efforts to strengthen its position in facing security challenges posed by the rise of China.